Influences of activation agent impregnated sewage sludge pyrolysis on emission characteristics of volatile combustion and De-NOx performance of activated char. (15th October 2015) - Chen, Hui; Chen, Dezhen; Hong, Liu
Highlights: Emission characteristics of volatile combustion from SS pyrolysis were investigated with and without activation agent impregnation. SO2, NO, N2 O and HCl are main emissions from SS pyrolysis volatile combustion. SO2 emission can be avoided when KOH and ZnCl2 is impregnated into SS before pyrolysis. Char produced from KOH-impregnated SS pyrolysis shows the best De-NOx efficiency. Abstract: In this study, KOH and ZnCl2 were impregnated into sewage sludge as activation agents to produce activated sludge char in the pyrolysis step for the De-NOx process. The emission characteristics of volatile combustion from the pyrolysis of raw sewage sludge (SS-Raw), sewage sludge spiked with KOH (SS-KOH), and sewage sludge spiked with ZnCl2 (SS-ZnCl2 ) were investigated. In addition, the De-NOx effects and the characteristics of the prepared chars, including specific surface areas, pore distributions, functional groups, were explored. The exploration results showed that the pollutants generated during the volatile combustion process could be divided into primary pollutants (SO2, NO, N2 O, and HCl) and minor pollutants (CO, NH3, and HCN). Under the conditions of oxygen-rich combustion, SO2 and NOx emissions from SS-KOH were 0% and 113.2% of those from SS-Raw respectively. SS-ZnCl2 exhibited the similar SO2 and NOx emissions to those of SS-KOH. However, SS-ZnCl2 released considerable HCl during the pyrolysis process, thus limiting its application. Sludge char from SS-KOH (SC-KOH) also exhibited the best De-NOx performance compared to the chars from SS-Raw and SS-ZnCl2 and the De-NOx efficiency was 56% higher than that of sludge char from SS-Raw (SC-Raw). Therefore, with KOH-impregnated SS, activated sludge char can be produced via one pyrolysis step and used in the De-NOx process.